2016
DOI: 10.17306/j.afs.2016.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation and treatment with precursors of phenolics synthesis improve low-molecular antioxidants and antioxidant capacity of buckwheat sprouts

Abstract: An increased interest has been noticed in the modifi cation of food along each step of its production (breeding, production technology, storage condition). Briefl y speaking nutritional properties as well as the level and activity of bioactive compounds present in plant-origin food may be modifi ed using a range of technological ELICITATION AND TREATMENT WITH PRECURSORS OF PHENOLICS SYNTHESIS IMPROVE LOW-MOLECULAR ANTIOXIDANTS AND ANTIOXIDANT CAPACITY OF BUCKWHEAT SPROUTS ABSTRACTBackground. Recently, an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Some previous studies indicated that jasmonic acid elicitation can increase the production of some phytochemicals (like phenolic compounds or vitamin C) in basil and lettuce leaves (Złotek et al, 2014;2016). Additionally, YE-elicited lettuce also showed an increase in total phenolic content, but not in vitamin C content .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Some previous studies indicated that jasmonic acid elicitation can increase the production of some phytochemicals (like phenolic compounds or vitamin C) in basil and lettuce leaves (Złotek et al, 2014;2016). Additionally, YE-elicited lettuce also showed an increase in total phenolic content, but not in vitamin C content .…”
Section: Discussionmentioning
confidence: 89%
“…Due to its high content of antioxidants, marjoram has antioxidant properties, which largely determine the health-promoting value of this herb (Vallverdú--Queralt et al, 2015). It is well known that elicitation may affect the antioxidant capacity of plant food (Świeca, 2016;. Elicitation with jasmonic acid significantly improved the antioxidant activity of the extracts of the herb, which was determined using two different assays: DPPH free radical scavenging activity and reducing power ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sprouting is an inexpensive and effective method to improve the nutritional quality and the phytochemical profiles of edible seeds [4]. The impact of germination on the functional properties of alfalfa and buckwheat has been investigated [4,5]. Owing to their numerous health benefits, an ongoing study on the sprouts is crucial to fully uncover the chemical composition and health functions of these products.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it also contains valuable trace elements (zinc, copper, manganese, iron, potassium, phosphorus, magnesium, boron, cobalt, and platinum) and dietary fiber [3,5]. Buckwheat is also a rich source of phenolics, such as rutin, quercetin, quercitrin, orientin, homoorientin, vitexin, and isovitexin-flavonoids with well-documented pro-health properties [6,7].…”
Section: Introductionmentioning
confidence: 99%